The Reflection on the Course “Management of Educational Organizations" - Alexandrova, Gulnara (Nazarbayev University Graduate School of Education, 7(1), 2024)
In the reflective paper of the course Management of Higher Education, I want to highlight some experiences I have had. Additionally, the paper reflects on some top ics and guest lecturers’ professional experience which was informative and valuable for me personally and pro fessionally. The process of internally analyzing and in vestigating a problem that has been brought about by an experience, which clarifies and produces meaning in terms of the self, and which leads to a shift in conceptu al perspective, is called reflective learning (Boyd & Fales, 1983). This reflection includes four main themes: budg eting, marketing, human resources, and group project work. In the course, I have learned all these aspects the oretically and practically.
Keywords: reflective learning; Management of Higher Education